2022
DOI: 10.1021/acsnano.2c07448
|View full text |Cite
|
Sign up to set email alerts
|

Chain Redistribution Stabilizes Coexistence Phases in Block Copolymer Blends

Abstract: The nanoscale morphologies of block copolymer (BCP) thin films are determined by chain architecture. Experimental studies of thin film blends of different BCP chain types have demonstrated that blending can stabilize new motifs, such as coexistence phases. Here, we deploy coarse-grained molecular dynamics (MD) simulations in order to better understand the self-assembly behavior of BCP blend thin films. We consider blends of lamella- and cylinder-forming BCP chains, studying their morphological makeup, the chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…This partitioning can be thought of as the result of highly localized enrichment of BCP chains directed by the chemical pattern template. In the absence of external directing fields, energetic penalties associated with chain stretching or compression due to chain mixing promote localized enrichment of cylindrical and lamellar BCP chains within a thin film blend of lamellar and cylindrical BCPs of nearly equivalent molecular weight, as used here, leading to the self-assembly of coexisting dot and lines patterns ( 24 , 36 ). On the other hand, a chemical pattern template with features nearly commensurate with the BCP domains imposes a strong directing field that can enforce the assembly of a single pattern type (i.e., lines or dots), aligned and registered with the template, which minimizes chain distortion while satisfying surface wetting constraints ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This partitioning can be thought of as the result of highly localized enrichment of BCP chains directed by the chemical pattern template. In the absence of external directing fields, energetic penalties associated with chain stretching or compression due to chain mixing promote localized enrichment of cylindrical and lamellar BCP chains within a thin film blend of lamellar and cylindrical BCPs of nearly equivalent molecular weight, as used here, leading to the self-assembly of coexisting dot and lines patterns ( 24 , 36 ). On the other hand, a chemical pattern template with features nearly commensurate with the BCP domains imposes a strong directing field that can enforce the assembly of a single pattern type (i.e., lines or dots), aligned and registered with the template, which minimizes chain distortion while satisfying surface wetting constraints ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using coarse-grained molecular dynamics (MD) simulations, we have previously shown that highly localized chain redistribution and enrichment at the scale of single morphological objects in thin film blends of cylindrical and lamellar BCPs stabilizes coexistence phases (i.e., dots and lines) ( 36 ). We therefore used MD simulations to investigate the assembly behavior of a blend of “L” (symmetric) and “C” (asymmetric) BCP chains on a wide range of chemical patterns analogous to those used experimentally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), which allows them to form coexistence phases. 84,85 We studied thin film blends of cylinder-forming (C) and lamellar-forming (L) polystyreneblock-poly(methyl methacrylate) (PS-b-PMMA), and found that the interplay of blending and substrate surface energy can be used to control the morphology that arises. We first consider the assembly of a thin film of pure C67 (cylinder-forming PS-b-PMMA with total molecular weight of 67 kg mol À1 ) as a function of film thickness (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…79,80 Blending in the bulk has proven to be a viable means of engineering the morphology, [81][82][83] since the mixture of chains can redistribute to stabilize what would otherwise be highenergy structural motifs. In thin films, blends can exhibit coexistence phases, 84,85 and chemical gratings can be used to select which phase forms. 86 Average surface chemistry influences the orientation 36,87,88 and feature size 89 of singlecomponent BCP films.…”
Section: Introductionmentioning
confidence: 99%